2008
DOI: 10.1007/s11414-008-9122-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Evidence-Based Practices for Treatment of Alcohol and Drug Disorders: The Role of the State Authority

Abstract: The current climate of increasing performance expectations and diminishing resources, along with innovations in evidence-based practices (EBPs), creates new dilemmas for substance abuse treatment providers, policymakers, funders, and the service delivery system. This paper describes findings from baseline interviews with representatives from 49 state substance abuse authorities (SSAs). Interviews assessed efforts aimed at facilitating EBP adoption in each state and the District of Columbia. Results suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…This may reflect the extensive efforts at the policy level to encourage and support EBT exploration and implementation for substance abuse treatment programs more generally (Addiction Technology Transfer Center Network, 2014; Oregon Health Authority, 2015; Rieckmann et al, 2009; Substance Abuse and Mental Health Services Administration, 2015a, b) as well as efforts focused specifically on programs serving AI/AN communities (Addiction Technology Transfer Center Network, 2014; Oregon Health Authority, 2015). Certainly awareness and use of EBTs in these programs is far broader than suggested by thought leaders working in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the extensive efforts at the policy level to encourage and support EBT exploration and implementation for substance abuse treatment programs more generally (Addiction Technology Transfer Center Network, 2014; Oregon Health Authority, 2015; Rieckmann et al, 2009; Substance Abuse and Mental Health Services Administration, 2015a, b) as well as efforts focused specifically on programs serving AI/AN communities (Addiction Technology Transfer Center Network, 2014; Oregon Health Authority, 2015). Certainly awareness and use of EBTs in these programs is far broader than suggested by thought leaders working in this area.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an SSA may seek to assure the use of EBPs among providers that receive public dollars. A recent study found that many SSAs are concentrating more effort on strategies such as education, training, and infrastructure development and less effort on financial mechanisms, regulations, and accreditation (Rieckmann, Kovas, Fussell, & Stettler, 2008). Investment in workshop training alone is necessary but insufficient to ensure the adoption and implementation of an EBP (Walters, Matson, Baer, & Ziedonis, 2005); therefore, the ATTC model provides SSAs a framework that can be used to identify specific technology transfer activities and their intended objectives, determine which activities are most appropriate to their level of resource commitment, monitor the progress of efforts to support EBP implementation over time, and demonstrate accountability for stewardship of public resources.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…13,14 The means of information dispersion is also challenged in the substance abuse sector, with delays and ineffective methods of transmission as well as reduced resource allocations often cited as barriers. 2,4,5,15 Given these barriers to EBP adoption and implementation among community-based addiction treatment providers, as well as the higher percentage of vulnerable populations served in the community-based model (resulting in greater levels of staff-stress), it is possible that addiction treatment providers in centers that provide services to specific vulnerable populations (such as those who are homeless, those with comorbid mental health disorders, racial and ethnic minorities, and women) may have more negative attitudes about EBPs. This is the focus of the study presented here: to use regression analyses methods to examine whether serving a higher percentage of vulnerable populations is associated with addiction treatment program directors' attitudes toward evidence-based pharmacological treatment.…”
Section: Introductionmentioning
confidence: 99%